The Erosive Oral Lichen Planus Treatment with Nd:YAG Laser Combined with Total Glucosides of Paeony - Lien Qi; Xing Wang; Qian Deng (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
Background: To investigate the clinical effect of Nd:YAG laser combined with total glucosides of paeony (TGP) for the treatment of erosive oral lichen planus (OLP).  Study Design: Sixty patients diagnosed with erosive OLP with clinical symptoms were divided into an observation group (n=28) and a control group (n=32) using a random number table. All erosive OLP patients received TGP while only the patients in observation group subjected to Nd:YAG laser. The clinical effects were evaluated comparatively three months before and after the treatment.  Results: Three months after the treatment, the visual analogue scales (VAS) score and sign score for observation group improved significantly to (1.36±0.89) points and (2.32±1.56) points respectively. The average VAS score and sign score for the control group were (2.75±1.67) and (3.66±1.33) points. In both groups, the results of treatments were tended to be significantly better than before (P<0.05). The average VAS score and sign score were superior to those in the control group (P<0.05). The effectiveness for the observation group was significantly higher than the control group (82.1% vs. 53.1%).  Conclusion: Nd:YAG laser combined with TGP can improve the efficiency of the treatment for erosive OLP. The scheme is safe and effective and worth expanding in clinical practice.